1997
DOI: 10.1002/hep.510250424
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of preconditioning on the injury associated to hepatic ischemia-reperfusion in the rat: Role of nitric oxide and adenosine

Abstract: Both adenosine and NO are synthesized in vascular endoThe effects of ischemic preconditioning on rat liver thelium and are released into the surrounding vascular and integrity, as well as the implication of nitric oxide (NO) interstitial compartments during the ischemic and reperfuand adenosine in this process, has been evaluated. Presion periods. Experimental data suggest that NO is a major conditioning before ischemia-reperfusion prevented the mediator of adenosine-induced vasodilatation. 9 In addition, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
290
1
15

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(320 citation statements)
references
References 17 publications
13
290
1
15
Order By: Relevance
“…Recent work by our group, using a model of hepatic preconditioning in rat, demonstrated that inhibition of NO abolishes the effect of preconditioning. 8 In the same study, we suggested that NO production was stimulated by endogenous adenosine. It is known that pretreatment with adenosine or selective adenosine A 1 receptor agonists mimics the effect of preconditioning in heart.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Recent work by our group, using a model of hepatic preconditioning in rat, demonstrated that inhibition of NO abolishes the effect of preconditioning. 8 In the same study, we suggested that NO production was stimulated by endogenous adenosine. It is known that pretreatment with adenosine or selective adenosine A 1 receptor agonists mimics the effect of preconditioning in heart.…”
mentioning
confidence: 87%
“…Reflow was initiated by removal of the clamp. 8 The studies performed were in compliance with the European Union regulations for animal experiments. …”
mentioning
confidence: 99%
“…Experiments, mainly performed in the heart, suggest a number of substances as potential ligands, including adenosine, bradykinin, catecholamines, reactive oxygen species, opiods, angiotensin II, and NO [68]. With regard to the liver, adenosine has thus far been considered the major player in triggering preconditioning [62,63,65,69,70]. Adenosine is a breakdown product of ATP that is released in large quantities into the extracellular space within seconds of the onset of ischemia.…”
Section: Protective Mechanisms Of Early Ischemic Preconditioningmentioning
confidence: 99%
“…A 1 and A 2 receptors have been chiefly implicated in the ischemic preconditioning of the myocardium and liver, respectively [62,63,65,69,71].…”
Section: Protective Mechanisms Of Early Ischemic Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation